Utveckling av en språkinlärningsapplikation inom maritim engelska – Genom en användar-centrerad design process - Carlsson, Elias; Pham, Hanna (My University, 2023)
This report presents the methodology, the work done and the results achieved during the development of Maritime English application. The purpose of this project is to develop an application that can be downloaded on a mobile phone. The goal of the application is to provide various exercises that can help students to learn Maritime English, including defining, pronouncing and listening to Standard Marine Communication Phrases (SMCP) as well as identify different ship parts. The application is developed on the Flutter framework along with open-source design material to ensure that future Chalmers students have the opportunity to continue the development of the application. The main focus of the application is implementing exercises for learning ship vocabulary. The results in an application that allows students to learn ship vocabulary through various exercises. The application also provides definitions of SMCP phrases, pronunciation practice and listening to SMCP. The application follows the project owner’s requirements and there is potential to expand it with more exercise for SMCP phrases.